Apparatus of Capture: Music and the Mimetic Construction of Social Reality in the Early Modern/Colonial Period. Issue 1 (April 2022) - Vélez, Daniel Villegas
Abstract : This paper supplements Gebauer and Wulf's analyses of mimesis as a mechanism for the construction of social reality. After situating archaic musical mimesis in the context of Homeric performance and its critique in Plato, I demonstrate how musical mimesis functions as an assemblage of inscription of social mores and values through two case studies. The first examines how this mimetic mechanism is actualised in the 1589 Medici intermedi as an allegorical apparatus of capture that enables the sovereign to control the space and time of the performance. The second examines how this apparatus is redeployed by seventeenth-century Jesuit missionaries in South America to coerce nomadic Indigenous peoples into settlements known as 'reducciones'. The paper advances an account of the darker role of musical mimesis in the dissymmetrical construction of social reality during the baroque: as a world-making tool of sovereign power and a world-destroying mechanism of epistemic genocide in colonised territories.